Influence of Pollutants from Transport on Life Expectancy in the EU Countries - Rozehnalová, Hana; Mádr, Michal; Formanová, Lucie; Andrlík, Břetislav (Problemy Ekorozwoju, 2021)
Road transport has become the major source of environmental pollution and it is also one of the biggest environmental risks in the EU countries. Good air quality is very important for population as pollutants have negative impacts on human health. The paper deals with relationship between air pollutants generated by road transport and the life expectancy in EU countries. At the beginning of the paper the main pollutants from motor vehicles are described and impact on human health is summarized too. We use regression analysis of panel data to analyse the relationship between chosen air pollutants and life expectancy. Our results show negative impacts of nitrogen oxide and sulphur oxide, specifically reduction in life expectancy by 1.49 years for nitrogen oxides and 0.28 years for sulphur oxides with an increase of the pollutant by 1%. So according to our findings economic policy makers should focus primarily on the reduction of nitrogen and sulphur oxides.